A study on linguistic features of metonymic expressions of human body parts in “for whom the bell tolls” by ernest hemingway and their vietnamese translational equivalents. - Nguyễn,Mai Sương (ĐHĐN., 2015)
his study investigated the syntactic and semantic features of metonymic expressions of human body parts in “For Whom the Bell Tolls” and their Vietnamese translational equivalents in “Chuông nguyện hồn ai” translated by Nguyen Vinh and Ho The Tan. This is a descriptive study focusing on finding the diversity of metonymic expressions of human body parts in “For Whom the Bell Tolls” in both languages. In the framework of cognitive linguistics, 400 collected samples of sentences or phrases containing MEOHBPs were qualitatively and quantitatively analyzed to find out the syntactic and semantic features of metonymic expressions of human body parts in “For Whom the Bell Tolls” and their Vietnamese translational equivalents. The findings showed that syntactically, metonymic expressions of human body parts can be a subject, a verb phrase, a direct object, a preposition object. Semantically, there could be different kinds of relations between a Part for the Whole, a Part for a Part , a container- things contained, producer- the product and there were two basic types of conventional conceptual mapping of metonymy: source -in- target domain (types of part for person metonymy) and the target -in- source domain (types of mapping of whole for part metonymy). Besides, it can be claimed that meaning extension often takes place on the basis of conceptual metonymy. The metonymy serves as cognitive links between two or more distinct senses of a word. Furthermore, teachers help learners to acquire the habit of using these MEOHBPs when they are translated into Vietnamese and the teachers should attract the learners’ attention to loss in meaning, and to cultural differences, help them discover these cases to have wider vision to translation and develop in the learners a lightened cultural consciousness. And learners should try to think of and use these MEOHBPs in the way English native speakers do.